Respuesta :

Answer:

vcbnvjhgbvnhtrgbhj hy6tyuk

Step-by-step explanation:

The correct answer is:  [D]: " (-5 )x − " .

_________________________________________________________

Explanation:

_________________________________________________________

" -1/2(-3/2x + 6x + 1) − 3x " ;

=  (-1/2 * -3/2 x) + (-1/2 * 6x) + (-1/2 * 1) − 3x ;  

=   [ (-1 *-3) /(2*2)] x + (-3x) + (-1/2) ] − 3x ;  

=   [ (3/4)x − 3x − (1/2) ] − 3x ;  

=   (3/4)x − 3x − (1/2) − 3x ;  

= ?? ;   →  Combine the "like terms" ;  

          → "(3/4)x − 3x − 3x " =   ?? ;

                        → "(3/4)x − 3x = "(-9/4)x";

                        → "(-9/4)x − 3x = "(-21/4)x "  =  " (-5 )x " ;  

→  The answer is:  " (-5 )x −  " ;  

___________________________________________________

→   which is:

___________________________________________________  

→   Answer choice:  [D]:  " (-5 )x −  " .

___________________________________________________